Hybridized Time Series Modeling with Machine Learning Techniques for Pomegranate Price Fluctuations - S. Vishnu Shankar; Rajeev Ranjan Kumar; Mrinmoy Ray; V. Lavanya; R. Subash (Agricultural Research, 2026)

Unravelling subsurface complexity to characterize hard rock aquifers using electrical resistivity tomography - Joy Choudhury; Subash Chandra; S K Begum; E Nagaiah; Abhilash K Paswan (Journal of Earth System Science, 2026)

Evaluation of gamma irradiation effect on morpho-physiological and biochemical traits of dragon fruit (Selenecereus monacanthus) under water stress environment - Kuldeep K. Shukla; Kundan Kishore; K. Pradhan; Subash C. Swain; Manas R. Sahoo; Rajkumari Bhol; S. Samal; Ankita Sahu; Ashok Mishra (Plant Physiology Reports, 2025)

Investigation of inventive Quinoxaline-based fluorescent probe for detection of harmful chromium (VI) present in water and its bioapplications - J. Subash; Subhro Mandal; C.M. Vineeth Kumar; S. Sathvika; V. Karthick; Souvik Pal; Shamima Hussain; Amrita Pal; Animesh Pramanik; Subhenjit Hazra (Journal of Environmental Chemical Engineering, 2025)

Plant derivative extracts'(Brahmastra) spectral characterization and their impact on Lipaphis erysimi and natural enemies in oilseed-mustard under organic farming conditions - Subash Singh; Mehra S. Sidhu (Organic Agriculture, 2025)

Development and characterization of contraction-suppressed full-thickness skin wound model in rabbits - Khan Sharun; S. Amitha Banu; Merlin Mamachan; Athira Subash; Mathesh Karikalan; Rohit Kumar; Obli Rajendran Vinodhkumar; Kuldeep Dhama; A.M. Pawde; Amarpal (Tissue and Cell, 2024)

Assessment of species migration patterns in forest ecosystems of Tamil Nadu, India, under changing climate scenarios - Ramachandran A.; Mithilasri Manickavasagam; Hariharan S.; Mathan M.; Ahamed Ibrahim S.N.; Divya Subash Kumar; Kurian Joseph (Theoretical and Applied Climatology, 2024)

High mortality in free-ranging wild boars associated with African swine fever virus in India - K. G. Sai Balaji; M Karikalan; S Saravanan; S Mahajan; K Rajeshkumar; Mirza Vaseem; Sushmita Nautiyal; Athira Subash; Kirtika Sharma; Sanchay Kumar Biswas; Sukdeb Nandi; Abhijit M Pawde; et al. (Archives of Virology, 2024)

Sustainable Wastewater Management via Biochar Derived from Industrial Sewage Sludge - Shubham S. Kulkarni; Neelaambhigai Mayilswamy; Sumati Sidharth; Alsha Subash; Anwesha Satapathy; Balasubramanian Kandasubramanian (Circular Economy and Sustainability, 2024)

Heterogeneous wettable degummed silk fibers engineered with electrospun superhydrophobic PLA for efficacious oil/water separation - S. Rastogi; A. Subash; B. Kandasubramanian (International Journal of Environmental Science and Technology, 2024)

Microplastic sources, formation, toxicity and remediation: a review - Ahmed I. Osman; Mohamed Hosny; Abdelazeem S. Eltaweil; Sara Omar; Ahmed M. Elgarahy; Mohamed Farghali; Pow-Seng Yap; Yuan-Seng Wu; Saraswathi Nagandran; Kalaivani Batumalaie; Subash C. B. Gopinath; Oliver Dean John; et al. (Environmental Chemistry Letters, 2023)
Microplastic pollution is becoming a major issue for human health due to the recent discovery of microplastics in most ecosystems. Here, we review the sources, formation, occurrence, toxicity and remediation methods of microplastics. We distinguish ocean-based and land-based sources of microplastics. Microplastics have been found in biological samples such as faeces, sputum, saliva, blood and placenta. Cancer, intestinal, pulmonary, cardiovascular, infectious and inflammatory diseases are induced or mediated by microplastics. Microplastic exposure during pregnancy and maternal period is also discussed. Remediation methods include coagulation, membrane bioreactors, sand filtration, adsorption, photocatalytic degradation, electrocoagulation and magnetic separation. Control strategies comprise reducing plastic usage, behavioural change, and using biodegradable plastics. Global plastic production has risen dramatically over the past 70 years to reach 359 million tonnes. China is the world's top producer, contributing 17.5% to global production, while Turkey generates the most plastic waste in the Mediterranean region, at 144 tonnes per day. Microplastics comprise 75% of marine waste, with land-based sources responsible for 80–90% of pollution, while ocean-based sources account for only 10–20%. Microplastics induce toxic effects on humans and animals, such as cytotoxicity, immune response, oxidative stress, barrier attributes, and genotoxicity, even at minimal dosages of 10 μg/mL. Ingestion of microplastics by marine animals results in alterations in gastrointestinal tract physiology, immune system depression, oxidative stress, cytotoxicity, differential gene expression, and growth inhibition. Furthermore, bioaccumulation of microplastics in the tissues of aquatic organisms can have adverse effects on the aquatic ecosystem, with potential transmission of microplastics to humans and birds. Changing individual behaviours and governmental actions, such as implementing bans, taxes, or pricing on plastic carrier bags, has significantly reduced plastic consumption to 8–85% in various countries worldwide. The microplastic minimisation approach follows an upside-down pyramid, starting with prevention, followed by reducing, reusing, recycling, recovering, and ending with disposal as the least preferable option.

A review of comparison between the traditional catalyst and zeolite catalyst for ammonia-selective catalytic reduction of NOx - M Sunil Kumar; MS Alphin; S Manigandan; S Vignesh; S Vigneshwaran; T Subash (Fuel, 2023)

A simplified geopolymer concrete mix design considering five mineral admixtures - N. Subash; S. Adish Kumar (European Journal of Environmental and Civil Engineering, 2022)

Influence of Different Nutrient Management Practices and Cropping Systems on Organic Carbon Pools in Typic Ustochrept Soil of Indo-Gangetic Plains in India - Debashis Dutta; A. L. Meena; Amit Kumar; N. Subash; R. P. Mishra; P. C. Ghasal; Jairam Choudhary; Chandra Bhanu; Raghavendra KJ; Chetan Kumar G; Ankur Kumar; Vaibhav Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Piperlongumine, a piper alkaloid, enhances the efficacy of doxorubicin in breast cancer: involvement of glucose import, ROS, NF-κB and lncRNAs - Nikee Awasthee; Anusmita Shekher; Vipin Rai; Sumit S. Verma; Shruti Mishra; Anupam Dhasmana; Subash C. Gupta (Apoptosis, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

Outcome of Public Hospital-Funded Continuous Positive Airway Therapy Device for Patients with Obstructive Sleep Apnoea: An Australian Perspective Study - Subash S. Heraganahally; Claire Kerslake; Siji Issac; Joy J. Mingi; Izaak Thomas; Lata Jayaram; Robert Adams (Sleep and Vigilance, 2020)

Epoxyazadiradione exhibit activities in head and neck squamous cell carcinoma by targeting multiple pathways - Vipin Rai; Sushil Kumar Aggarwal; Sumit Singh Verma; Nikee Awasthee; Anupam Dhasmana; Sadhna Aggarwal; Satya N. Das; Mangalam S. Nair; Sanjay Yadav; Subash C. Gupta (Apoptosis, 2020)

Building sustainability in the Eastern Himalaya: linking evidence to action - Sandeep Tambe; Gopal S. Rawat; Nima Tashi Bhutia; Pem Norbu Sherpa; Subash Dhakal; Sarika Pradhan; Himanshu Kulkarni; M. L. Arrawatia (Environment, Development and Sustainability, 2020)

Evaluation and bias corrections of gridded precipitation data for hydrologic modelling support in Kabini River basin, India - Subash Yeggina; Ramesh S. V. Teegavarapu; Sekhar Muddu (Theoretical and Applied Climatology, 2020)

A conceptually superior variant of Shepard's method with modified neighbourhood selection for precipitation interpolation - Subash Yeggina; Ramesh S. V. Teegavarapu; Sekhar Muddu (International Journal of Climatology, 2019)
The accuracy of gridded precipitation data depends on the availability of a uniformly spaced rain gauge network and an appropriate spatial interpolation method that considers the rainfall variability and other factors that influence the precipitation patterns in the region of interest. In the current study, conceptually superior variants of a widely used spatial interpolation algorithm, Shepard's method, are proposed, formulated and evaluated to overcome one of the major limitations in neighbourhood selection, that is, arbitrary selection of rain gauges. The variants provide mechanisms to objectively select the rain gauges (control points) based on correlation (variant 1), distribution similarity (variant 2) and a combination of both (variant 3). The improved variants were used in the development of gridded rainfall data at a resolution of 5 km over the Kabini River basin in south India, and in the state of Kentucky, United States. Results from multiple experiments using the original Shepard's method and its variants indicate improvements in the accuracy of precipitation estimates. Also, these variants have preserved the site‐specific statistics and distributional characteristics of the rainfall data. A variant 1 that uses a correlation‐based neighbourhood selection criterion performed better for daily and monthly data compared to others and is suitable for generation of gridded rainfall data. The variant 1 when used with information from clustering of sites for selection of the neighbours has led to improvement in gridded precipitation data estimates. The proposed variant 1 can also be used for point data estimation useful for filling missing data at any site.

Ecology and Use of Lantana camara in India - Girish C. S. Negi; Subrat Sharma; Subash C.R. Vishvakarma; Sher S. Samant; Rakesh K. Maikhuri; Ram C. Prasad; Lok M. S. Palni (The Botanical Review, 2019)

Transport and fate of microplastics in wastewater treatment plants: implications to environmental health - Subash Raju; Maddison Carbery; Aswin Kuttykattil; Kala Senathirajah; S. R. Subashchandrabose; Geoffrey Evans; Palanisami Thavamani (Reviews in Environmental Science and Bio/Technology, 2018)

Adoption of Modern Maize Varieties in India: Insights Based on Expert Elicitation Methodology - S. Pavithra; Christian Boeber; Showkat Ahmad Shah; S. P. Subash; P. S. Birthal; Surabhi Mittal (Agricultural Research, 2018)

Modelling the forest transition in Central Western Ghats, India - T. V. Ramachandra; Bharath Setturu; K. S. Rajan; M. D. Subash Chandran (Spatial Information Research, 2017)

Applicability of APSIM to capture the effectiveness of irrigation management decisions in rice-based cropping sequence in the Upper-Gangetic Plains of India - N. Subash; M. Shamim; V. K. Singh; B. Gangwar; B. Singh; D. S. Gaydon; C. H. Roth; P. L. Poulton; A. K. Sikka (Paddy and Water Environment, 2015)

Diagnostic Value of Lactate Levels in Acute Abdomen Disorders - Indu Verma; Satinder Kaur; Subash Goyal; Shweta Goyal; J. S. Multani; A. P. S. Narang (Indian Journal of Clinical Biochemistry, 2014)

Excitotoxicity in the Pathogenesis of Autism - M. M. Essa; N. Braidy; K. R. Vijayan; S. Subash; G. J. Guillemin (Neurotoxicity Research, 2013)

Comparative Study on Precipitation Techniques for Protease Isolation and Purification from Labeo rohita Viscera - S. Geethanjali; Anitha Subash (Journal of Aquatic Food Product Technology, 2013)

Observed variability and trends in extreme temperature indices and rice–wheat productivity over two districts of Bihar, India—a case study - N. Subash; S. S. Singh; Neha Priya (Theoretical and Applied Climatology, 2013)

Decadal frequency and trends of extreme excess/deficit rainfall during the monsoon season over different meteorological sub-divisions of India - N. Subash; H. S. Ram Mohan; A. K. Sikka (Hydrological Sciences Journal, 2011)

Trend detection in rainfall and evaluation of standardized precipitation index as a drought assessment index for rice–wheat productivity over IGR in India - N. Subash; H. S. Ram Mohan (International Journal of Climatology, 2011)
The frequency and intensity of meteorological droughts over the Indo‐Gangetic Region (IGR) of India pertaining to the rice crop during kharif season (June to July to October to November) and the wheat crop during the rabi season (November to December to March) were assessed using the standardized precipitation index (SPI). The monthly distribution of rainfall is more crucial than the cumulative seasonal rainfall on rice–wheat (RW) productivity. Consequently, an attempt was made to measure the effectiveness of using monthly SPI from June to September to assess drought on RW productivity over five major RW growing states of IGR in India. An attempt is also made to test the use of monthly SPI for the early kharif rice and rabi wheat forecasts for these states. The long‐term (1906–2005) mean annual rainfall of IGR is 1099.1 mm with a standard deviation of 115.7 mm and a coefficient of variation of 10.5%. It was observed that the kharif rice productivity index and monthly SPI from June to September have a significant ( R 2 = 0.44) multiple regression at 0.001 level over IGR. It was also observed that in the Indo‐Gangetic Region, the wheat productivity index and monthly SPI (June to September) have an insignificant ( R 2 = 0.21) multiple regression. It indicated that the monthly distribution of monsoon rainfall in terms of the SPI accounted for 44% yield variability in rice and 21% yield variability in wheat. Thus, these indices may be used for forecasting the productivity of the RW system over IGR states in India. Copyright © 2010 Royal Meteorological Society

A Simple Rationally Integrated Drought Indicator for Rice–Wheat Productivity - N. Subash; H. S. Ram Mohan (Water Resources Management, 2011)

An investigation into observational characteristics of rainfall and temperature in Central Northeast India—a historical perspective 1889–2008 - N. Subash; A. K. Sikka; H. S. Ram Mohan (Theoretical and Applied Climatology, 2011)

Integrated studies for characterization of lineaments used to locate groundwater potential zones in a hard rock region of Karnataka, India - Subash Chandra; V. A. Rao; N. S. Krishnamurthy; S. Dutta; Shakeel Ahmed (Hydrogeology Journal, 2006)

Integrated studies for characterization of lineaments used to locate groundwater potential zones in a hard rock region of Karnataka, India - Subash Chandra; V. A. Rao; N. S. Krishnamurthy; S. Dutta; Shakeel Ahmed (Hydrogeology Journal, 2006)